2017
DOI: 10.4103/2249-4863.220010
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Indian Diabetes Risk Score and its association with body mass index and glycosylated hemoglobin for screening of diabetes in and around areas of Lucknow

Abstract: Objectives:The present study aimed to assess the validity of Indian Diabetes Risk Score (IDRS) and its association with body mass index (BMI) and glycosylated hemoglobin (HbA1c) for screening of diabetes and obesity.Methodology:A cross-sectional study was designed, and samples were randomly enrolled from Lucknow and its adjoining areas. Totally, 405 subjects were included in the study. We used diabetes risk factors (age, waist circumference, physical activity, and family history of diabetes) for screening of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…This finding is similar to the finding of Khan MM et al in Lucknow (U.P) where waist circumferences of majority of males and females were more than the cut-off values. (14) In the present study, majority (82.39%) of study participants reported to be involved in mild physical activity while the rest were involved in sedentary activity (15.79%), strenuous activity (1.42%) and moderate activity (0.4%). In a study conducted in the same Kalyanpuri area by Singh A et al, majority (62.9%) of the study subjects were moderate workers and 31.2% were sedentary workers.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This finding is similar to the finding of Khan MM et al in Lucknow (U.P) where waist circumferences of majority of males and females were more than the cut-off values. (14) In the present study, majority (82.39%) of study participants reported to be involved in mild physical activity while the rest were involved in sedentary activity (15.79%), strenuous activity (1.42%) and moderate activity (0.4%). In a study conducted in the same Kalyanpuri area by Singh A et al, majority (62.9%) of the study subjects were moderate workers and 31.2% were sedentary workers.…”
Section: Discussionmentioning
confidence: 50%
“…This is in line with the findings of Khan MM et al and Singh A et al whereby majority of study subjects did not report any family history of diabetes. (14,15) This might be attributed to the unawareness of study subjects regarding previous history of diabetes in their families. However, this finding is alarming and stresses on the need of awareness generation along with appropriate dietary changes and lifestyle modification even among people with no previous family history, in view of this ever-increasing burden of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The chance of diabetes risk score was low (6.38%) among individuals who are underweight than obese (44.54%) with a statistical significant difference in the study done by Gupta SK, et al [ 17 ] Similarly, study conducted in Lucknow by Khan MM, et al , also suggested the association of risk of diabetes with BMI. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…28 Additional investigation is necessary to elucidate the complex mechanisms that contribute to the onset of preeclampsia and to investigate potential therapeutic approaches that target autonomic dysfunction and gestational diabetes mellitus in expectant women. 29 However, additional research is required to clarify the specific mechanisms at play and to formulate approaches for evaluating and intervening in the risk of these factors in expectant women 30 . It is imperative to comprehend the intricate relationship among gestational diabetes mellitus (GDM), autonomic dysfunction, and preeclampsia in order to guide clinical management during pregnancy and enhance outcomes for both mother and foetus.…”
Section: Discussionmentioning
confidence: 99%